Clinical significance of CDKN2A homozygous deletion in combination with methylated MGMT status for IDH‐wildtype glioblastoma. (10th April 2021) - Funakoshi, Yusuke; Hata, Nobuhiro; Takigawa, Kosuke; Arita, Hideyuki; Kuga, Daisuke; Hatae, Ryusuke; Sangatsuda, Yuhei; Fujioka, Yutaka; Sako, Aki; Umehara, Toru; Yoshitake, Tadamasa; Togao, Osamu; et al.
Abstract: Objective: Accumulating evidence from recent molecular diagnostic studies has indicated the prognostic significance of various genetic markers for patients with glioblastoma (GBM). To evaluate the impact of such genetic markers on prognosis, we retrospectively analyzed the outcomes of patients with IDH ‐wildtype GBM in our institution. In addition, to assess the impact of bevacizumab (BEV) treatment, we compared overall survival (OS) between the pre‐ and post‐BEV eras. Methods: We analyzed the data of 100 adult patients (over 18 years old) with IDH ‐wildtype GBM from our database between February 2006 and October 2018. Genetic markers, such as MGMT methylation status, EGFR amplification, CDKN2A homozygous deletion, and clinical factors were analyzed by evaluating the patients' OS. Results: CDKN2A homozygous deletion showed no significant impact on OS in patients with methylated MGMT status ( p = 0.5268), whereas among patients with unmethylated MGMT status, there was a significant difference in OS between patients with and without CDKN2A homozygous deletion (median OS: 14.7 and 16.9 months, respectively, p = 0.0129). This difference was more evident in the pre‐BEV era (median OS: 10.1 and 15.6 months, respectively, p = 0.0351) but has become nonsignificant in the post‐BEV era (median OS: 16.0 and 16.9 months, respectively, p = 0.1010) due to OS improvement in patients with CDKN2A homozygous deletion. However, these findings could not be validated in The Cancer Genome Atlas cohort. Conclusions: MGMT and CDKN2A status subdivided our cohort into three race‐specific groups with different prognoses. Our findings indicate that BEV approval in Japan led to OS improvement exclusively for patients with concurrent unmethylated MGMT status and CDKN2A homozygous deletion. Abstract : CDKN2A homozygous deletion showed no significant impact on OS in patients with methylated MGMT status, while, among patients with unmethylated MGMT status, there was a significant difference in OS between patients with and without CDKN2A homozygous deletion. This difference was more evident in the pre‐BEV era, but has become non‐significant in the post‐BEV era due to OS improvement in patients with CDKN2A homozygous deletion.